MODEL PENILAIAN DAN EVALUASI PELAKSANAAN DIKLAT BAGI PEGAWAI NEGERI SIPIL - Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2010)
Donalson Silalah, Basically, the government and local governments have made the development of government officers through a program of education and training. Providing education and training is less efficient and effective manner due to the relative unavailability of assessment guidelines and evaluation of education and training. Therefore, this paper aims to build a model of assessment and evaluation of education and training. Models are constructed focused on education and training participant, lecturer, curriculum, organizers and the participants after they return to duty at their respective workplaces. Model assessment and evaluation of education and training builds upon the indicators of each aspect. Indicators that are used can be adjusted as needed. Based on the models constructed can be known what the obstacles to the implementation of education and training. Based on the constraints that are found to be a solution in the subsequent implementation of education and training.